1998
DOI: 10.1161/01.res.82.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal–Regulated Kinases (ERK1/2) by Angiotensin II Is Dependent on c-Src in Vascular Smooth Muscle Cells

Abstract: Among the angiotensin II (Ang II)-mediated signal events likely to be important in vascular smooth muscle cells (VSMCs) is activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2). The upstream mediators by which Ang II activates ERK1/2 remain poorly defined. Recently, we showed that Ang II activated c-Src, a nonreceptor kinase, which is a candidate to mediate Ang II signal events. To determine whether c-Src is required for ERK1/2 activation by Ang II, we studied the effects of Src family-selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 35 publications
15
90
1
2
Order By: Relevance
“…These data support previous studies documenting an important role for Src-dependent tyrosine phosphorylation in PLC␥ activation and calcium mobilization in several cell types (50,54,55). In addition, results from our laboratory in SrcϪ/Ϫ cells and with c-Src inhibitors showed a correlation between decreased GIT1 tyrosine phosphorylation and activation of PLC␥ (23,26).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data support previous studies documenting an important role for Src-dependent tyrosine phosphorylation in PLC␥ activation and calcium mobilization in several cell types (50,54,55). In addition, results from our laboratory in SrcϪ/Ϫ cells and with c-Src inhibitors showed a correlation between decreased GIT1 tyrosine phosphorylation and activation of PLC␥ (23,26).…”
Section: Discussionsupporting
confidence: 92%
“…3E). These results are very similar to data previously published by our laboratory and others for protein phosphatase 1 in VSMC (23,26) and for protein phosphatase 2 in ECV304 cells (50), cardiac myocytes (51), and endothelial cells (52). We were unable to perform antisense GIT1 knockdown experiments in 293 cells because the endogenous level of GIT1 expression was too low to assay by Western blot (not shown).…”
Section: Git1 Phosphorylation Regulates Plc␥ 49938supporting
confidence: 92%
See 2 more Smart Citations
“…28 Angiotensin II stimulation was associated with a rapid activation of c-Src and activation of MAPK in vascular smooth muscle cells. 29 PI-3K activation may be upstream of Ras activation, and PI-3K may be involved in the function of Src, Shc, and Grb2. 30 It has been reported that the p110 subunit of PI-3K binds to an effector domain of Ras in vitro, 30 and the PI-3K inhibitor wortmannin reduced insulin-induced MAPK activity.…”
Section: Role Of Ptk Mapk and Pkc In Cerebral Vasospasmmentioning
confidence: 99%